Colorectal cancer diagnostics: biomarkers, cell-free DNA, circulating tumor cells and defining heterogeneous populations by single-cell analysis. (July 2013) - Kin, Cindy; Kidess, Evelyn; Poultsides, George A; Visser, Brendan C; Jeffrey, Stefanie S
Reliable biomarkers are needed to guide treatment of colorectal cancer, as well as for surveillance to detect recurrence and monitor therapeutic response. In this review, the authors discuss the use of various biomarkers in addition to serum carcinoembryonic antigen, the current surveillance method for metastatic recurrence after resection. The clinical relevance of mutations including microsatellite instability, KRAS, BRAF and SMAD4 is addressed. The role of circulating tumor cells and cell-free DNA with regards to their implementation into clinical use is discussed, as well as how single-cell analysis may fit into a monitoring program. The detection and characterization of circulating tumor cells and cell-free DNA in colorectal cancer patients will not only improve the understanding of the development of metastasis, but may also supplant the use of other biomarkers.